Drying Spirulina with Foam Mat Drying at Medium Temperature - Aji Prasetyaningrum; Mohamad Djaeni (International Journal of Science and Engineering, 2012)
Spirulina is a single cell blue green microalgae (Cyanobacteria) containing many Phytonutrients (Beta-carotene, Chlorophyl, Xanthophyl, Phyocianin) using as anti-carcinogen in food. Producing dry spirulina by quick drying process at medium temperature is very important to retain the Phytonutrient quality. Currently, the work is still challenging due to the gel formation that block the water diffusion from inside to the surface.  This research studies the performance of foam-mat drying on production of dry spirulina. In this method the spirulina was mixed with foaming agent (glair/egg albumen, popular as white egg) at 2.5% by weight at air velocity 2.2 m/sec. Here, the effect of spirulina thickness and operational temperature on drying time and quality (Beta-carotene and color) were observed. The drying time was estimated based on the measurement of water content in spirulina versus time. Result showed that the thicker spirulina, the longer drying time. Conversely, the higher operational temperature, faster drying time. At thickness ranging 1-3 mm and operational temperature below 70oC, the quality of spirulina can fit the market requirement